iPod touch made simple iOS 5 Edition - Trautschold, Martin (Apress, 2011)
The new iOS 5-driven iPod touch devices are much more than just music. These have all the features of a PDA?including email, calendar, Google Maps, the App Store, and even phone capabilities?as well as the ability to watch movies and play your favorite games, all packed into Apple?s sleek design. With iPod touch Made Simple, iOS 5 Edition, you'll learn how to take advantage of all these features and more, now available using the new iOS 5. Packed with over 1,000 visuals and screenshots, this book will help you master all the functions of the iPod touch devices that run iOS 5 and teach you time-saving techniques and tips along the way. Written by two successful smartphone trainers and authors, this is the go-to guide for the iPod touch!